Pengaruh CAR, NPF Dan FDR Terhadap Return Bagi Hasil Deposito Mudharabah Pada Perbankan Syariah Di Indonesia Periode 2019-2021 Dengan Profitabilitas Sebagai Variabel Moderating - Hasanah, Aulia; Nasution, Juliana; Kamilah, Kamilah (Universitas Labuhanbatu, 2023)
This study aims to determine the effect of CAR, NPF, FDR on returns for mudharabah deposits in Islamic banking in Indonesia for the 2019-2021 period with profitability as a moderating variable. The population of this study were 12 Islamic banking companies. The sampling method used was the purposive sampling method so that 10 sample companies were obtained for 3 years of observation (2019-2021). The results of this study partially show a significant influence between the CAR, NPF and FDR variables on the return on mudharabah deposits. The results of this study indicate that there is a simultaneous influence of CAR, NPF and FDR on the returns for mudharabah deposits. The moderating test shows that Profitability moderates the relationship between CAR, NPF and FDR on returns for mudharabah deposits.